A Systematic Review and Meta-Analysis of the Language and literature - Claire Kaplaan (Al-Qanṭara, 2022)
Purpose: This systematic review and meta-analysis estimates the overall lan- guage skills of youth offenders involved with the juvenile justice system. Given the importance of this population, identifying avenues through which we can increase the likelihood of successful interventions is a necessary societal effort. Method: Eighteen studies, representing data from 3,304 individuals, contributed 82 effect sizes to the current analytic sample. We used random-effects models to estimate the overall mean effect size metric to address each research ques- tion and fit meta-regression models for each moderator analysis. Results: Results yielded that youth offenders presented with significantly lower language skills than their nonoffending peers ( g = −1.26). Furthermore, high pro- portions of the present meta-analytic sample were classified as youth with mod- erate (50%) and severe (10%) language disorders. In general, differences in lan- guage skills did not vary as a function of age, gender, or language measure type. We did detect significant differences as a function of sample country and type of peer comparison group.